Paul's letters and contemporary Greco-Roman literature: theorizing a new taxonomy - Robertson, Paul (Supplements to Novum Testamentum, 2016)
Preliminary Material /Paul M. Robertson -- Introduction /Paul M. Robertson -- 1 Paul, Paul’s Letters, and Contemporary Greco-Roman Literature of the Ancient Mediterranean /Paul M. Robertson -- 2 Rethinking Paul and Paul’s Letters: Paul, Epictetus, and Philodemus in Context /Paul M. Robertson -- 3 How Do We Compare Literature? Re-Classifying Paul’s Letters in a Socio-Literary Sphere /Paul M. Robertson -- 4 An Overview of the Data: Annotated Literary Criteria in Paul, Epictetus, Philodemus, and Other Pauline Comparanda /Paul M. Robertson -- 5 Socio-Historical Implications of Textual Comparison: The Education and Lives of Paul, Epictetus, and Philodemus /Paul M. Robertson -- Conclusion: Socio-Literary Spheres and Literary Classification in Biblical and Classical Studies /Paul M. Robertson -- Appendix /Paul M. Robertson -- Bibliography /Paul M. Robertson -- Index of Terms /Paul M. Robertson -- Index of Ancient Authors and Texts /Paul M. Robertson.